MODELING IMMISCIBLE FLUID DISPLACEMENT IN A POROUS MEDIUM USING LATTICE BOLTZMANN METHOD - Atykhan, Magzhan (Nazarbayev University School of Engineering and Digital Sciences, 2021)
The numerical analysis of the gas displacing immiscible liquid in 2D homogenous porous media is demonstrated. The model is analyzed in terms of different flow and pore geometry specifications, namely capillary number (Ca), liquid – gas viscosity ratio (D), surface wettability, and the pore domain's geometrical properties. The research intends to extend the understanding of complex multiphase flow in a porous domain with various physical parameters. The analysis was conducted using a 2D homogenous porous medium with seven-column circular- or square-shaped obstacles, representing the pores' solid wall. The model is constructed using pseudopotential Lattice Boltzmann Method (LBM) in Peng-Robinson's (P-R) EOS framework. One pore from the first column is removed to simulate more realistic flow behavior. Additionally, small perturbations between neighboring pores were added. This work demonstrates that the gaseous phase penetration into the pore domain certainly depends on the aforementioned physical parameters. It was found that higher Ca and the surface wettability increases the effective gaseous phase penetration while increasing liquid-gas viscosity ratio leads to the opposite effect.
Keywords: 2D homogenous porous media; liquid – gas viscosity ratio; capillary number; pore geometry specifications; Lattice Boltzmann Method; Peng-Robinson's (P-R) EOS framework; Type of access: Open Access; Research Subject Categories::TECHNOLOGY